Etika Menuntut Ilmu Dalam Kitab Ta’lim Muta’allim Dan Aktualisasinya Pada Santri Pondok Pesantren Darul Muta’allimin Tanah Merah - Mardiah, Mardiah (Yayasan Abdurrauf Cendekia Nusantara, 2024)
This research aims to find out how the ethics of seeking knowledge in the Book of Ta'lim Muta'allim and how to actualize the ethics of seeking knowledge in the Darul Muta'allimin Islamic Boarding School, Tanah Merah. In this study, the author uses qualitative research methods, data taken by observation/observation techniques, interviews and questionnaires. The results of the study found that the Actualization of Ethics of studying at the Darul Muta'allimin Tanah Merah Islamic Boarding School is like the attitude of the students when in the classroom including: being silent, being polite (Ta'zim) and listening to the teacher's explanation, but there are also those who are busy talking to their friends even until they fall asleep, asking questions when the question session has been opened, but there are also students who interrupt the teacher's words who are talking. Ethics that have been applied by Santri when in the Pondok such as: Stopping when crossing paths with the teacher, the attitude of the student when called by the teacher, the attitude of the student when the teacher is angry because of the student's poor behavior, and asking for permission when he wants to leave the Boarding School.Referring to the sharing of the evidences that are put forward that the ethics of a student towards the teacher during the ongoing learning process at the Darul Muta'allimin Islamic Boarding School are not fully appropriate because it is still contrary to the Ethics of Demanding Knowledge in the Book of Ta'lim Muta'allim [Penelitian ini bertujuan untuk mengetahui Bagaimana Etika Menuntut Ilmu dalam Kitab Ta’lim Muta’allim dan Bagaiman Aktualisasi Etika Menuntut Ilmu di Pondok Pesantren Darul Muta’allimin Tanah Merah. Dalam penelitian ini, Penulis menggunakan metode penelitian kualitatif, data yang diambil dengan teknik observasi/pengamatan, wawancara dan angket. Hasil penelitian menemukan bahwaAktualisasi Etika menuntut ilmu di Pondok Pesantren Darul Muta’allimin Tanah Merah seperti sikap para santri ketika didalam kelas diantaranya: diam, bersikap sopan (Ta’zim) dan menyimak penjelasan guru namun ada juga yang sibuk sendiri berbicara dengan temannya bahkan sampai tertidur, bertanya ketika telah dibuka sesi pertanyaan namun ada juga santri yang memotong perkataan Guru yang sedang bicara. Etika yang telah diterapkan Santri ketika berada dalam Pondok seperti: Berhenti ketika sedang berpapasan dengan guru, sikap murid ketika dipanggil guru, sikap murid ketika guru marah sebab perilaku murid yang kurang baik, dan meminta izin ketika ingin keluar Pondok.Merujuk dari berbagi dalil-dalil yang di kemukakan bahwa Etika seorang murid terhadap guru ketika proses pembelajaran yang sedang berlangsung di Pondok Pesantren Darul Muta’allimin belum sepenuhnya sesuai karena masih bertentangan dengan Etika-etika Menutut Ilmu dalam Kitab Ta’lim Muta’allim].